Prevalence of Baseline Polymorphisms for Potential Resistance to NS5A Inhibitors in Drug-Naive Individuals Infected with Hepatitis C Genotypes 1–4. Issue 1 (January 2015) - McCormick, Adele L; Wang, Lawrence; Garcia-Diaz, Ana; Macartney, Malcolm J; Webster, Daniel P; Haque, Tanzina
Background: The non-structural 5A (NS5A) protein of HCV is a multifunctional phosphoprotein involved in regulation of viral replication and virion assembly. NS5A inhibitors targeting domain I of NS5A protein have demonstrated high potency and pan-genotypic antiviral activity, however they possess a low genetic barrier to resistance. At present, only genotype 1, the most prevalent HCV genotype has been studied in detail for resistant variants. Methods: Utilizing a panel of genotypic-specific resistance assays, population sequencing was performed on plasma-derived viral RNA isolated from 138 patients infected with HCV genotypes 1–4 and not treated with direct-acting antiviral agents. Amino acid changes in HCV NS5A domain I at codon positions 28, 30, 31, 32 and 93, reported to confer reduced susceptibility to certain NS5A inhibitors were examined. Additionally, genotypic outcome based on NS5A sequences were compared with VERSANT HCV Genotype Assay (LiPA) 1.0 (Siemens Healthcare Diagnostics, Surrey, UK) and Abbott m2000 RealTi m e HCV genotype II assay (Abbott Molecular, Maidenhead, Berkshire, UK). Results: Amino acid substitutions associated with moderate to high level resistance to NS5A inhibitors were detected in 2/42 (4.76%) HCV-1a, 3/23 (13.04%) HCV-1b, 4/26 (15.38%) HCV-2, 1/24 (4.17%) HCV-3 and 1/23 (4.35%) HCV-4 infected patients who had not been treated with NS5A inhibitors. Genotype prediction based on NS5A sequences were concordant with LiPA and/or Abbott Real-Ti m e for 97.10% of cases. Conclusions: Primary resistance mutations associated with resistance to first-generation NS5A inhibitors such as daclatasvir were observed in all genotypes, albeit at low frequencies. An excellent correlation based on NS5A genotyping and LiPA or Abbott Real-Ti m e was achieved.